Physiological and Productivity Performances of Japanese Quails Supplemented with Cassava Leaf Paste - L. Jumadin; H. Maheshwari; N. Ulupi; A. S. Satyaningtijas (Faculty of Animal Science, Bogor Agricultural University, 2022)
This study aimed to evaluate and analyze the physiological performances of quails raised under this temperature range and then given cassava leaf paste to reduce the heat stress effects. The variables measured were blood chemical, stress indicators, body resistance, productivity, and quality of quail eggs. This experiment used 160 quails in a completely randomized design with 4 doses of cassava leaf paste as treatments with 4 replications, namely P0 (0 mg/g), P1 (5.29 mg/g), P2 (10.58 mg/g), and P3 (15.87 mg/g). The administration of cassava leaf paste for 30 days was carried out through 100 mL of drinking water for each dose. The results showed that administering various doses of cassava leaf paste to quails increased blood glucose and lower blood cholesterol concentrations. Administration of cassava leaf pastes in P3 treatment increased the oxygen saturation value of quail by 6.14% compared to the control treatment. Malondialdehyde (MDA) serum concentration as an indicator of oxidative stress significantly increased at a higher dose (P3) of cassava leaf paste administration. Meanwhile, the superoxide dismutase (SOD) serum concentration remains the same. Administration of cassava leaf pastes in P3 treatment decreased liver MDA by 66.66%, and P2 treatment increased liver SOD by 3.85% compared to the control treatment. The clearance test showed the presence of cassava leaf paste increased by 1.2% the death of Salmonella pullorum bacteria. The provision of cassava leaf paste can increase egg productivity and quality. The total cholesterol of egg yolks of quails receiving cassava leaf paste was lower than the control. In conclusion, applying cassava leaf paste can support the physiological performance such as blood chemistry (glucose levels, cholesterol, and oxygen saturation), stress indicators (serum and liver MDA and SOD concentrations), body resistance (total leukocyte count and the death rate of Salmonella pullorum bacteria), of quails, thereby increasing the productivity and quality of quail eggs.